The results of the self-care behavior promotion program for glaucoma patients to control intraocular pressure at Phrae Hospital: - - Intararujikul, Taratip (Journal of Phrae Public Health for Development - วารสารสาธารณสุขแพร่เพื่อการพัฒนา, 2025)
The quasi-experimental research aims to study results of the self-care behavior promotion program for glaucoma patients to control intraocular pressure at Phrae Hospital that affects for the glaucoma knowledge, perception of severity and benefits of glaucoma prevention and treatment and self-care behavior between before and after joining the program in 45 people selected by purposive sampling. Research instruments were the self-care behavior promotion program for glaucoma patients to control intraocular pressure and the questionnaire consisted of 4 parts: 1) General information, 2) Knowledge about glaucoma with a KR-20 value of 0.94, 3) Perception of disease severity and benefits of glaucoma prevention, and 4) Self-care behaviors for glaucoma with Cronbach's alpha coefficient values of 0.95 and 0.91, respectively. Data was analyzed by descriptive statistics and paired t–test. The result that after joined the self-care behavior promotion program for glaucoma patients to control intraocular pressure at Phrae Hospital. The sample were had the glaucoma knowledge, perception of severity and benefits of glaucoma prevention and treatment and self-care behavior increasing. It is significantly different from before joining the program (p < 0.00). Should encourage perception of disease severity and benefits of glaucoma prevention in glaucoma patients to continuously control intraocular pressure at home.